Prevalence of Metabolic Syndrome in Patients with Subclinical and Overt Hypothyroidism Visiting Tertiary Care Centre of Western Nepal - Jha, Amit Chandra; Koirala, Kedar Nath; Jayan, Archana; Gautam, Narayan; Dubey, Raju Kumar; Tamang, Binaya; Pokhrel, Buddhi Raj (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Hypothyroidism is a syndrome resulting from thyroid hormone deficiency. Metabolic syndrome (MetS) is a cluster of metabolic abnormalities is associated with increased risk for atherosclerotic cardiovascular disease (CVS) and type 2 diabetes mellitus. Thyroid hormones are major regulatory hormones that control the rate of metabolic function; thus, alteration in the levels of these hormones may be associated with MetS. The objective of our study was to find out the prevalence of MetS in subclinical and overt hypothyroidism. MATERIAL AND METHODS: A hospital-based cross sectional study was conducted at Universal College of Medical Sciences Teaching Hospital (UCMS-TH) Bhairahawa from March to September 2019. A total of 222 hypothyroid patients were enrolled in this study. MetS was diagnosed by National Cholesterol Education Program-Adult Treatment Panel III (NCEP-ATP III; 2005) revision criteria. The anthropometric indices were recorded. fT3, fT4 and TSH were measured by chemiluminescence immunoassay (CLIA) method and other biochemical parameters were estimated by colorimetric method. Data were analyzed by using SPSS 16.0. RESULTS: Patients were aged between 10 and 60 years, with a mean age of 38.89 years. The prevalence of MetS was 44.1% of which 80.6% were females. Furthermore, the prevalence of MetS was found to be 43.7% in subclinical hypothyroidism and 46.6% in overt hypothyroidism. CONCLUSION: The prevalence of MetS is high in both overt and subclinical hypothyroidism. Screening for MetS in patients with hypothyroidism can reduce the risk for CVD, as well as the mortality rate and mortality associated with it.